Rapid detection of human chromosome 21 aberrations by in situ hybridization. - Lichter, P (1988)
Plasmid clones containing up to 94 kilobases of single-copy DNA from band q22.3 of chromosome 21 and a complete pool of insert DNA from a chromosome 21 recombinant library have been used to rapidly detect numerical and structural aberrations of chromosome 21 by in situ hybridization in both metaphase and interphase cells. A trisomic karyotype, diagnostic of Down syndrome, is readily detected in nonmitotic cells because the majority of their nuclei exhibit three discrete foci of hybridization, in contrast to normal diploid cells, which show two foci. Chromosomal translocations involving chromosome 21 sequences were also detected with these probes, and the intranuclear location of 21q22.3 DNA sequences in "normal" human brain neurons was established with the plasmid DNA probe set. These results suggest that chromosome 21-specific probes may have utility in clinical diagnostics, especially by facilitating the direct analysis of interphase cells.